2015
DOI: 10.1007/s00198-015-3141-y
|View full text |Cite|
|
Sign up to set email alerts
|

Alendronate sodium/vitamin D3 combination tablet versus calcitriol for osteoporosis in Chinese postmenopausal women: a 6-month, randomized, open-label, active-comparator-controlled study with a 6-month extension

Abstract: SummaryThis study compares efficacy of ALN/D5600 versus that of calcitriol in osteoporotic Chinese postmenopausal women. ALN/D5600 produced greater bone mineral density (BMD) increases, greater bone turnover marker decreases, and less vitamin D insufficiency. This study provided detailed clinical information regarding ALN/D5600 treatment versus calcitriol 0.25 μg/day. The study did not evaluate fracture risk.IntroductionThe aim of this study is to investigate efficacy of alendronate 70 mg/vitamin D3 5600 IU co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Few studies had evaluated the effects of vitamin D or calcium supplements on urinary calcium levels. Zhenlin Zhang found 8.4% and 13.9% of patients developed hypercalciuria in postmenopausal osteoporosis patients treated with ALN/D5600 or calcitriol 0.25 μg/d plus calcium 500 mg/d for 12 months, respectively . In patients treated with GCs, the incidence of hypercalciuria was higher than postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies had evaluated the effects of vitamin D or calcium supplements on urinary calcium levels. Zhenlin Zhang found 8.4% and 13.9% of patients developed hypercalciuria in postmenopausal osteoporosis patients treated with ALN/D5600 or calcitriol 0.25 μg/d plus calcium 500 mg/d for 12 months, respectively . In patients treated with GCs, the incidence of hypercalciuria was higher than postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of bisphosphonate and vitamin D analog shows a synergistic effect on skeletal and muscular systems, which is possibly due to the difference in the mode of action between these two regimens [ 13 ]. The previous randomized, controlled study conducted by the investigators also revealed that the ALN/D5600 combination was superior to calcitriol alone in PMO women with respect to BMD gain and bone turnover reduction [ 9 ]. Moreover, a subgroup analysis confirmed the difference in predictive factors for BMD response after 12-month treatment with ALN/D5600 vs. calcitriol [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The original study was a 6-month, randomized, open-label, active-comparator-controlled, parallel-group study with a 6-month extension to evaluate the efficacy and safety of weekly ALN/D5600 as a combination tablet vs. 0.25 μg of calcitriol daily in the treatment of osteoporosis in postmenopausal women in China (protocol number 264–01, clinicaltrials.gov number NCT01350934). The study protocol, design and inclusion/exclusion criteria were as previously reported [ 9 ]. Briefly, eligible patients were patients who were > 55 years of age and postmenopausal for at least one year, with no prior antiresorptive therapies, patients who had no prior hip fracture, patients who had no pronounced medical history other than osteoporosis, and patients had no uncontrolled primary/secondary hyperparathyroidism (as examined by iPTH at screening) or evidence of metabolic bone disease other than postmenopausal osteoporosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 8 ] A previous randomized, open label, controlled study demonstrated in Chinese postmenopausal women with osteoporosis that weekly alendronate 70 mg/vitamin D 3 5600 IU (ALN/D5600) resulted in a significantly greater increase in lumbar spine BMD (LS-BMD) and a greater reduction in bone turnover marker (BTM) measurements than daily 0.25 μg calcitriol alone within 1 year, although the benefit regarding the reduction in fracture risk remains to be investigated. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%